Changes in chemical composition during storage of squashes and pumpkins - Pedrosa, Josué Fernandes; Casali, Vicente Wagner Dias; Cheng, Simon Suhwen; Chitarra, Maria Isabel Fernandes; Carvalho, Vânia Déa de (Pesquisa Agropecuaria Brasileira, 2014)
Changes in chemical composition were determined during storage of squashes (Curcubita maxima, Duch.) and pumpkins (Curcubita moschata, Duch.) for 70 days. The hybrid ’Tetsukabuto’ was used as standard. During the storage period, total soluble solids and beta-carotene increased whereas starch content decreased; reducing sugars and non-reducing sugars increased up to 35 days and then decreased; total sugars and ratio total sugars/starch increased up to 56 days and then decreased at day 70. The hibrid ’ESAL 7511 x ESAL 7523’ gave similar chemical composition to ’Tetsukabuto.